Context influences the processing of verb transitivity in French sentences: more evidence for semantic−syntax interactions - MAGNE, CYRILLE; BESSON, MIREILLE; ROBERT, STÉPHANE (Language and cognition, 2014)
The influence of semantic context on verb argument structure processing was investigated in two experiments using both ERP and behavioral measures. Participants were presented with sentences ending with syntactically and/or semantically congruous or incongruous noun phrases and they were asked to judge the overall acceptability of the sentences. Syntactically incongruous sentences contained an intransitive verb followed by a direct object (e.g., *L’ennemi a conspiré (INTR) un complot *‘The enemy conspired a scheme’). In line with our hypothesis, results showed that the processing of syntactic incongruities was influenced by the degree of semantic congruency between the different sentence constituents (strong in Experiment 1 and weak in Experiment 2). Thus, the same syntactic incongruity was processed differently depending upon the semantic context of the sentence, thereby demonstrating the influence of semantic context on syntactic processing. We propose a linguistic account of the differential effects of verb transitivity as a function of the semantic context based upon Cognitive Construction Grammar and Frame Semantics.